Sustainable Strategic Alliance Partner Selection Using a Neutrosophic-Based Decision-Making Model: A Case Study in Passive Component Manufacturing. (23rd April 2022) - Lo, Huai-Wei; Chang, Dong-Shang; Huang, Lee-Te
Abstract : The electronics manufacturing industry is in an era of collaborative thinking and rapid change, as the rise of strategic alliances (SAs) plays a critical role in supply chain management. Strategic alliance (SA) collaboration is one of the most common strategies in the electronics industry, helping companies to complement each other. Most organizations or alliances operate together to produce more beneficial technologies for mutual benefit based on the sustainability thinking, such as in the areas of 5G, electric vehicles, aerospace, and smart healthcare. As the prompt evolution of information technology and electronics has a deep impact on global business activities, selecting partners based on a sustainability perspective is an urgent task. This paper proposes a complete sustainable SA partner selection framework to select the optimal partners. A neutrosophic-based decision-making model is used in the analysis. The neutrosophic ITARA technique is proposed to generate a set of criteria objective weights, and the neutrosophic TOPSIS technique is applied to determine the performance and priority of sustainable SA partners. This study introduces neutrosophic fuzzy logic to reflect the uncertainty in complex problems. Real-world data from a multinational passive component manufacturing company are used for case demonstration and analysis. The framework and methodology proposed in this study have many contributions to the electronics industry, including the establishment of assessment criteria, the identification of criteria, and the provision of partner selection practices. For academic research, the proposed model can be replicated in other areas of assessment and selection issues.